ANALISIS PENERAPAN JUAL BELI BAI SALAM DALAM MENINGKATKAN KESEJAHTERAAN PETANI - Tiara Pitri; Eja Armaz Hardi; Fauzan Ramli (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
Salam buying and selling transactions are a form of buying and selling transactions with payment in advance and delivery of goods at a later date in accordance with the price, specifications, quantity, quality, residence and place of delivery, as well as previously agreed in the contract. Salam buying and selling transactions are transactions that are usually carried out by the people of Rantau Alai Village when the sale and purchase of palm oil is agreed. This research is entitled "Analysis of the Application of Buying and Selling Ba'i Salam in Improving Farmers' Welfare". The aim of this research is to determine the implementation of palm oil buying and selling transactions in Rantau Alai Village, to find out how Ba'i Salam reviews palm oil buying and selling transactions in Rantau Alai Village, to find out whether the implementation of Ba'i Salam Buying and Selling can improve farmer welfare. This research uses a qualitative method with a descriptive approach, in sampling the researcher uses a sample selection technique with the provisions of the characteristics and characteristics of the objects in the research, while the data collection technique is by observation, interviews and documentation. The research results show that the palm oil buying and selling transactions implemented in Rantau Alai village are in the form of cash and credit transactions (Ba'i Salam). Implementation of Salam buying and selling transactions in Rantau Alai Village. Although the Ba'i Salam buying and selling transactions have not been implemented by all tokes in Rantau Alai Village, the community admits that the Ba'i Salam buying and selling system has helped and provided relief to the community.